The Evolution of Economies – Changes in The Structure of The Real Economic System - Piotr WALĄG (Communications of International Proceedings, 2020)
The article reflects the diversity of issues related to real changes in the structure of the economic system in market economies of highly developed countries, which underwent a strong phase of industrialisation, and then relocations of industrial production (to countries with cheaper labour factor), revealing as the first (the United States and the United Kingdom) in their economies the presence of the deindustrialisation process. As well as in the evolution of the market economy of developing countries, which are entering the deindustrialisation phase prematurely. The presentation of the most important issues of structural changes at the cognitive level allows us to attempt to outline possible interpretations of the effects for the countries under study and to assess the evolution of their economies, and above all the changes in the structure of employment at the empirical level, as well as to identify the main determinants, their individual patterns of changes in the structure of the economic system, and development. On the basis of the analysis of changes within the main sectors of the economy, changes in their share in total employment for the whole economy in the period 1970-2019 were examined for selected key countries. Using the regression analysis of structural change models, the main determinants of individual development patterns and the course of evolution of economies were examined and interpreted based on the results of the research.
Keywords: industrialisation; relocation; deindustrialisation; economic evolution; employment structure; patterns of changes in the structure of the real economic system.